Regulation of myonuclear positioning and muscle function by the skeletal muscle-specific CIP protein - Liu, Jianming; Huang, Zhan-Peng; Nie, Mao; Wang, Gang; Silva, William J.; Yang, Qiumei; Freire, Paula P. [UNESP]; Hu, Xiaoyun; Chen, Huaqun; Deng, Zhongliang; William, T.; Wang, Da-Zhi (Natl Acad Sciences, 2020)
The appropriate arrangement of myonuclei within skeletal muscle myofibers is of critical importance for normal muscle function, and improper myonuclear localization has been linked to a variety of skeletal muscle diseases, such as centronuclear myopathy and muscular dystrophies. However, the molecules that govern myonuclear positioning remain elusive. Here, we report that skeletal muscle-specific CIP (sk-CIP) is a regulator of nuclear positioning. Genetic deletion of sk-CIP in mice results in misalignment of myonuclei along the myofibers and at specialized structures such as neuromuscular junctions (NMJs) and myotendinous junctions (MT.Is) in vivo, impairing myonuclear positioning after muscle regeneration, leading to severe muscle dystrophy in mdx mice, a mouse model of Duchenne muscular dystrophy. sk-CIP is localized to the centrosome in myoblasts and relocates to the outer nuclear envelope in myotubes upon differentiation. Mechanistically, we found that sk-CIP interacts with the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex and the centriole Microtubule Organizing Center (MTOC) proteins to coordinately modulate myonuclear positioning and alignment. These findings indicate that sk-CIP may function as a muscle-specific anchoring protein to regulate nuclear position in multinucleated muscle cells.
Keywords: skeletal muscle; nuclear positioning; sk-CIP protein; LINC complex; MTOC